Discrete Likelihood Ratio Order for Power Series Distribution - Ameli, Narjes; Jarrahiferiz, Jalil; Mohtashami-Borzadaran, Gholam Reza (Revista Colombiana de Estadística, 2014)
It is well-known that some discrete distributions belong to the power series distribution (PSD) family, so it seems useful to study conditions to establish the discrete likelihood ratio order for this family. In this paper, conditions to some cases of PSD family under which the discrete likelihood ratio order we have looked at the holds. Also, we study the discrete version of the proportional likelihood ratio as an extension of the likelihood ratio order. Then we compare some members of the PSD family by discrete proportional likelihood ratio order.